THE INFLUENCE OF FINANCIAL TECHNOLOGY AND FINANCIAL LITERATURE ON BUSINESS SUSTAINABILITY - Triyani Budyastuti (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2021)
Micro, Small and Medium Enterprises (MSMEs) have a big role as an effort to increase economic development in Indonesia, economic growth and open up new jobs. The going concern of a company is the main objective of a business entity since the establishment of the business entity. The survival of a business entity is closely related to how management manages the company, both from financial and non-financial factors. This study aims to examine the effect of financial technology (fintech) and financial literacy on the business sustainability of micro, small and medium enterprises (MSMEs) in East Sudimara Village. The population in this study were all assisted MSMEs registered in East Sudimara Village. Researchers used the saturated sample method, in which the population was sampled. The primary data collection method used is a questionnaire method. The data analysis technique used in this study is multiple regression analysis techniques with a test instrument using PLS 3.0. The results of the study show that there is no influence of fintech and financial literacy on business continuity. This gives a signal to the government as a regulator, academics as educators, the private sector as a catalyst, and the community as a driver to socialize and develop fintech and financial literacy in MSMEs in East Sudimara Village in particular.